Safe vascular and bronchial division techniques for VATS uniportal lung resections - BATIREL, HASAN FEVZİ (AME PUBL CO, 2017)
VATS anatomic lung resections are becoming the standard of care for lung cancer with a long record of safety, feasibility, oncological adequacy. Following the multi-port VATS, uniportal VATS resections are becoming popular. However, uniportal VATS approach has unique challenges concerning vascular anatomy, angle of traction, stapler insertion and safe division of vessels and bronchi. In this article we are presenting a systematic description of technique for safe vascular and bronchial division for VATS uniportal anatomic resections. All operations were performed through a 3-5 cm utility incision at 5th intercostal space, using thoracoscopic and open surgical tools and endoscopic harmonic scalpel. After preparation of a vessel for division, a vascular tape was placed around the vessel and appropriate retraction for safe stapler orientation and passage was provided through intrathoracic manipulation of the vascular tape using a systemic approach. Bronchus was divided with the principle of cartilage to membranous approximation. Safe vascular and bronchial division are the most critical points for VATS lobectomy/segmentectomy operations. Uniportal VATS approach imposes additional geometric challenges for stapler orientation and placement due to further restriction of access, equipment crowding and hilar anatomy. Our technique provides practical solutions for uniportal lung resection.
Keywords: VATS; lung resections; uniportal approach; vascular; bronchial division; LOBECTOMY